Toxicological Aspects of Sorbates : A Review - Sri Raharjo (agriTECH, 1994)
Sorbic acid its sodium or potassium salts (sorbates) are still commonly used in preserved foods of plant or animal origin. It effectively inhibits the growth of yeast and mold species in processed foods pose no health hazard when properly used. According to published literatures, it is clear that sorbates are less toxic than other commonly used antimicrobial agents, because sorbic acid is metabolized in mammals in a similar way as other fatty acid such as caproic acid. For comparison, the LD50 of sodium chloride in rats is 5 g/kg body weight, while the LD50 of sorbic acid and potassium sorbate Is 10.5 and 6.2 g/kg body weight, respectively. Therefore, consumers, food processors and regulatory agencies should not considered sorbates as the most dangerous "public enemy". Proper method and.levels of use should always be advised.